Optimal Legislative Funding - Garcia, Beatriz Silva (2016)
We propose a model to study government formation by a legislative body composed by parties elected with a proportional representation rule. Once the legislative configuration is determined, the elected parties must form a government, choose a government policy and a distribution of legislative resources and benefits among the elected parties through a bargaining game. A mass of voters is assumed capable of voting strategically. Our goal is to study how a limitation on the available resources among legislators may affect the behavior of the agents involved in this system, both voters and legislators. We show that a decrease in the relative distance between ideologies increases the social welfare and decreases the necessary amount of resources to keep the optimal agreement. Moreover, there is an upper limit to this amount when the ideological distance increases